Penggunaan ROC pada Skrining Pre-Eklampsia dengan Metode USG DVAUT pada Ibu Hamil di Puskesmas Mulyorejo Surabaya - Intan Laraswati; Diah Indriani (Universitas Airlangga, 2019)
Pre-eclampsia is the third highest cause of death in pregnant women. Symptoms of pre-eclampsia can be identified by the presence of hypertension, proteinuria and edema during pregnancy until postpartum. Pre-eclampsia cannot be identified with certain risk factors, and cannot be prevented. Pre-eclampsia can be detected early using the pre-eclampsia screening method with sonography. The sonographic device used is referred to as DVAUt ultrasound (Uterine Artery Doppler Velocimetry Ultrasonography). This studying an analytic observational research with a cross sectional study design. The population was all pregnant women who examined at the Mulyorejo primary health center in 2013 until the first quarter of 2018. The sampling technique was consecutive sampling with inclusion and exclusion criteria. The number of samples obtained is 496 data. The study aimed to determine the sensitivity and specificity of the pre-eclampsia screening method using DVAUt ultrasound in detecting the tendency of pregnant women to experience pre-eclampsia. The data were analyzed of sensitivity and specificity and the Receiver Operating Characteristics (ROC) curve with p <0.001. P1GF / sFlt-1 (Gold standard) biomaker test sensitivity of 89% and specificity of 90%. The results of this study were the sensitivity of pre-eclampsia screening at 99.7% and specificity of 81.9%. The ROC method obtained the results of pre-eclampsia screening using DVAUt ultrasound has a high sensitivity and specificity in detecting the tendency of pregnant women to experience pre-eclampsia. Suggestions for research to refresh knowledge and procedures for conducting pre-eclampsia screening checks.